Jurnalisme Multikultural: Gagasan Mengembangkan Cara Pendekatan Pengkajiannya - Amirudin Amirudin (Endogami: Jurnal Ilmiah Kajian Antropologi, 2018)
THIS- article is meant to provoke how the discourse of multiculturalism as a cultural conception can be realized in journalism practice on TV stations. This idea is important to conclude how multiculturalism can be represented in newscast products in which produced by media actors. Through the concept of field (Bourdieu 1993, 2005), which explains how this ideas can be practiced into some models of multicultural journalism that can create some cultural products in the form of multicultural news on TV stations. The method used is certainly the ethnography to reveal how the practice of multicultural journalism among media people at TV stations is already on the certain level, by conducting interviews and close observation on every movement of news actors especially for religious, cultural, and political issues.